Analysis of Body Shapes and Physical Activity Dominant Patterns in a Coloring Books Collection - Vladimir Martínez Bello (Pensar en Movimiento)
Curriculum materials play an important role in the construction of the concept of the body to the extent that they are transmitters of knowledge, ideas and values. The aim of the study was to analyse whether the images in a collection of coloring books entitled The Boys´ Doodles Book and The girl´s Doodles Book show sexist stereotypes about body models and dominant patterns of physical activity. An independent observational group studied the images of the body through content analysis with a coding scheme using categories (gender, age, somatotype, space and type of physical activity) previously adopted by experts. The Boys´ Doodles Book shows an adult man with different body types, while women are not represented. In both books, the bodies do not maintain a preferred location. The Girls´Doodles Book represents a higher percentage of girls with a slender body, while men, who were under-represented, assume different body types. The Girls´Doodles Book tends to represent women in physical activities or sports with an artistic component. In conclusion, the images in both coloring books, promote sexist body shapes and physical activities. It is a warning to parents and mothers, as well as publishing houses, libraries and government agencies to critically analyse underlying patterns on coloring books.